MOTIVASI DAN KESIAPAN BELAJAR DALAM PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Novita Tyas Suviana (Bajang Institute, 2021)
This study examines motivation and readiness of learning in online learning during the Covid-19 pandemic. In the learning process, motivation and readiness to learn are needed so that learning can run well. Motivation can arise from the individual (intrinsic) or from outside the individual (extrinsic). Meanwhile, learning readiness includes physical, psychological and material readiness. During the Covid-19 pandemic, the online learning process has many obstacles that can affect students' motivation and readiness to learn. From the research results obtained, the obstacles during online learning are influenced by several factors such as technological capabilities, internet network access connections, learning media, student capacity in online learning, and a less conducive environment so that motivation and readiness to learn decreases. Someone’s motivation can affect the readiness to learn. Thus, it can be concluded that learning motivation in online learning during the pandemic has decreased. This leads to reduce learning readiness, so, it is needed the effort to increase the student learning motivation by the teacher